Korelasi Hypoxia Inducible Factor- 1A (HIF-1A) dan Vascular Endothelial Growth Factor (VEGF) Dengan Hasil Operasi pada Kanker Ovarium Jenis Epitel - RIVANY, RIZA (Indonesian Journal of Cancer, 2014)
Hypoxia inducible factor 1Î± (HIF-1Î±) regulates gene involved inresponse to hypoxia and promotes angiogenesis. HIF-1Î± is atranscriptional factor to induce vascular endothelial growth factor(VEGF). The objective of this study was to examine the correlation ofHIF-1Î± and VEGF expression with surgical outcome in epithelialovarian cancer, therefore could predict optimality of debulking inovarian cancer.Thirty patients with epithelial ovarian cancer who underwent primarysurgery were included in this study. Tumor tissues were obtainedfrom surgery and examined with q reverse transcriptase polymerasechain reaction (qRT-PCR) for HIF-1Î± and VEGF expression analysis.Evaluation of surgical outcome was based on volume of residualtumor. Correlation between HIF-1Î± and VEGF was analyzed by usingSpearman correlation test while the correlation between HIF-1Î± andVEGF and surgical outcome was analyzed by ANOVA.Results: The mean age of the study subjects was 47.53Â±10.41 years.Eleven patients (36.7%) were diagnosed with stage I ovarian cancer,9 patients (30%) with stage II, 8 patients (26.7%) stage III and 2patients (6.7%) with stage IV. Out of 30 patients, 22 patients (73.3%)successfully underwent optimal debulking and 8 patients (26.7%)with suboptimal debulking. There was a correlation between HIF-1Î±and VEGF expression (r=0.582) but no correlation between HIF-1Î±and VEGF expression with surgical outcome in patients withepithelial ovarian cancer.Conclusion: There was a significant correlation between HIF-1Î± andVEGF expression but no significant correlation between HIF-1Î± andVEGF expression with surgical outcomes.